Standards-Based DevOps Automation and Integration Using TOSCA - Wettinger, Johannes; Breitenbucher, Uwe; Leymann, Frank (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
DevOps is an emerging paradigm to tightly integrate developers with operations personnel. This is required to enable fast and frequent releases in the sense of continuously delivering software. Users and customers of today's Web applications and mobile apps running in the Cloud expect fast feedback to problems and feature requests. Thus, it is a critical competitive advantage to be able to respond quickly. Beside cultural and organizational changes that are necessary to implement DevOps in practice, tooling is required to implement end-to-end automation of deployment processes. Automation is the key to efficient collaboration and tight integration between development and operations. The DevOps community is constantly pushing new approaches, tools, and open-source artifacts to implement such automated processes. However, as all these proprietary and heterogeneous DevOps automation approaches differ from each other, it is hard to integrate and combine them to deploy applications in the Cloud. In this paper we present a systematic classification of DevOps artifacts and show how different kinds of artifacts can be transformed toward TOSCA, an emerging standard in this field. This enables the seamless and interoperable orchestration of arbitrary artifacts to model and deploy application topologies. We validate the presented approach by a prototype implementation, show its practical feasibility by a detailed case study, and evaluate its performance.